RANCANG BANGUN APLIKASI PEMBELAJARAN BISNIS ONLINE BERBASIS MOBILE PADA MASTER ONLINE COMMUNITY JAKARTA - Dadang Iskandar Maulana; Asep Ovid Afidin (STIKOM CKI, 2021)
Distance learning media or e-learning is not just limited to the use of computers alone, with communication utilization on mobile devices (mobile phones) enables the development of e-learning features. Advances in information technology in various learning processes are utilized to improve the quality of learning for members of the Online Community Masters, but in the learning process is still using conventional learning methods that are only done at regular meetings in office workshops. In conventional learning is very difficult for members who are far from the reach of workshop office. By utilizing the internet and mobile phone technology android can support the development of self- learning distance, especially by prioritizing the ease, flexibility and interactivity between users. Researchers use SWOT analysis (Strength, Weakness, Opportunity, Threat) to analyze strengths, weaknesses, opportunities and threats, so that researchers can conclude that with the application of android-based e-learning is expected to improve the learning process and activities of community members. E-learning applications can access content in the form of learning materials in the form of text, images and video and can also see the material without any limitations by space and time to learn.